Cultural Views of a Society Through Taylor Swift’s Song - Daniel Ginting; Eldana Reza Levana (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
Songs as cultural products function to help people to fulfil their needs. When people listen to the songs, they both enjoy the melody and also lyrics of the songs. Songs serve as tools to achieve different essential objectives such as changing moods, relating, and shaping their own identity. In this research, the writer studies deixis in song lyrics from the selected song in Taylor Swift's Folklore album: Cardigan, the Last Great American Dynasty, August, Illicit Affairs, and Betty. The analysis deixis of this study reveals a variety of life issues is treated directly or is strongly involved in the content of the lyrics of songs. This study found that lyrics have undergone dramatic changes when the influence of other cultures is unavoidable. This is an issue of significant interest and concern for parents and educators.